1999
DOI: 10.1542/peds.103.3.686
|View full text |Cite
|
Sign up to set email alerts
|

Circumcision Policy Statement

Abstract: ABSTRACT. Existing scientific evidence demonstrates potential medical benefits of newborn male circumcision; however, these data are not sufficient to recommend routine neonatal circumcision. In circumstances in which there are potential benefits and risks, yet the procedure is not essential to the child's current well-being, parents should determine what is in the best interest of the child. To make an informed choice, parents of all male infants should be given accurate and unbiased information and be provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(6 citation statements)
references
References 117 publications
0
4
0
2
Order By: Relevance
“…Sünnet genel anestezi veya lokal anestezi altında yapılmaktadır. Batı toplumlarında çoğunlukla genel anestezi ile yapılırken, ülkemiz gibi gelişmekte olan ülkelerde lokal anestezi daha fazla tercih edilmektedir (10,11) . (12) .…”
Section: Discussionunclassified
“…Sünnet genel anestezi veya lokal anestezi altında yapılmaktadır. Batı toplumlarında çoğunlukla genel anestezi ile yapılırken, ülkemiz gibi gelişmekte olan ülkelerde lokal anestezi daha fazla tercih edilmektedir (10,11) . (12) .…”
Section: Discussionunclassified
“…26 The policy statements from the American Academy of Pediatrics and the Canadian Pediatric Society likely influenced this decline. [5][6][7]27 A more recent study of 69 100 neonates in Ontario born in 1993-1994, found a prevalence rate of 44%; 26 there was evidence of declining hospital-based circumcision rates among male infants <28 days old in Ontario during the 1990s (in-hospital prevalence of 39% from 1989-1992 and 30% from 1994-1995 26 ). In 2007, estimation of number of Canadian males aged 15 or older circumcised for non-religious reason was reported as 30% 28 and may have changed slightly since then.…”
Section: To Keep or Not To Keep The Prepuce: The Circumcision Factormentioning
confidence: 99%
“…This is especially true as circumcision rates amongst infants continues to decline, from 85% of babies in 1985 to 32% in 2009, and the bandwagon effect of so-called "prepuce envy" becomes irrelevant (9). Furthermore, the American Academy of Pediatrics specifically states in their policy on circumcision that it is in no way essential to the well-being of a child (27).…”
Section: A Natural and Legal Rights Critiquementioning
confidence: 99%
“…However, other surgical and non-surgical treatments exist with high success rates, with lower cost and lesser morbidities than circumcision, such as the use of steroid topical cream; nevertheless, most cases of phimosis are physiologic in nature, and understanding the distinction between these types of phimosis can prevent overdiagnosis and unnecessary circumcision, as gentle retraction and normal washing over time can serve to treat physiologic phimosis (55)(56)(57). Furthermore, penises that have not been forcibly retracted are statistically no more prone to UTIs than circumcised penises, and overall an uncircumcised male is less than 1% more likely to get a UTI than a circumcised male, with the highest prevalence seen at less than one year of age (27,54). One study concludes that it would take 195 circumcisions to prevent one UTI (58).…”
mentioning
confidence: 99%
See 1 more Smart Citation